Transshipment capstone project - Ching Sánchez, Jacmara Katheryn (Universidad Tecnológica de Panamá, 2013)
The purpose of this project was to create a simulation model that replicated as much as possible the operations involved in the movement of containers between the ports and the railway in the country. By creating this replication, the intention was to study and identify the bottlenecks and problems in the different stages. As well as to experiment on the potential effects of changes in the operations such as number of resources, schedules, etc. For an easier understanding and management of the simulation, the model was divided into two major blocks: the port block and the rail block. These two blocks were then combined into one to observe the behavior of the complete system. The port block recreates the operations in the three major Panamanian ports: Balboa, Cristobal and Manzanillo; while the rail block recreates the operations of the Panama Canal Rail Company that travels across Panama from the Pacific Ocean to the Atlantic Ocean side and back. After analyzing different basic scenarios for both the port and rail operations certain factors that characterize these operations have been found. Having loading resources working in the three tracks in Balboa simultaneously causes an increase of around 24% in the throughput of trains per day compared to having the resources work dedicated to one track at a time. Having 20 additional trucks transporting containers from the port yard to the rail stack provides an increase of 7% in the throughput of the northbound train operations. It was determined that 60 trucks in Balboa is the limit where adding more trucks does not provide any more benefits. Adding an RTG provided an 8% increase in throughput whereas removing an RTG did not cause a conspicuous negative impact on the system. On the other hand, adding a top loader accounted for a 6% increase in the throughput meanwhile removing one decreased the throughput by 4%. In order to have a more conctusive result about what may be the limiting resources and difficulties on this complex system, further analysis and more data gathering is recommended. Note that the train operations were only simulated northbound, hence the loading of containers in the Atlantic side and unloading of these containers were estimated. Overall this document presents a fairly complete and complex simulation that suggests further study of specific resource utilization and operational strategies that would very likely yield a more efficient system while at the same time providing a robust building block for simutating transshipment systems in Panama or simitar operations etsewhere.